Propionate Protects against Lipopolysaccharide-Induced Mastitis in Mice by Restoring Blood–Milk Barrier Disruption and Suppressing Inflammatory Response - Wang, Jingjing; Wei, Zhengkai; Zhang, Xu; Wang, Yanan; Yang, Zhengtao; Fu, Yunhe (Frontiers in Immunology, 2017)
Mastitis, an inflammation of the mammary glands, is a major disease affecting dairy animal worldwide. Propionate is one of the main short chain fatty acid (SCFAs) that can exert multiple effects on the inflammatory process. The purpose of the study is to investigate the mechanisms underlying the protective effects of sodium propionate against Lipopolysaccharide (LPS)-induced mastitis model in mice. The data mainly confirm that inflammation and blood-milk barrier breakdown contribute to progression of the disease in this model. In mice with LPS, sodium propionate attenuates the LPS-induced histopathologic changes, inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) production, myeloperoxidase (MPO) activity in mammary tissues. Given their importance in the blood-milk barrier, tight junction proteins occludin and claudin-3 are further investigated. Our results show that sodium propionate strikingly increases the expressions of occludin and claudin-3 and reduces the blood-milk barrier permeability in this model. Furthermore, in LPS-stimulated mouse mammary epithelial cells (mMECs), LPS increased the expressions of phosphorylated (p)-p65, p-IκB proteins, which is attenuated by sodium propionate. Finally, we examine the possibility that propionate acts as a histone deacetylase (HDAC) inhibitor, the results show that both sodium propionate and trichostatin A (TSA) increase the level of histone H3 acetylation and inhibit the increased production of TNF-α, IL-6 and IL-1β in LPS-stimulated mMECs. These data suggest that sodium propionate protects against LPS-induced mastitis mainly by restoring blood-milk barrier disruption and suppressing inflammation via NF-κB signaling pathway and HDAC inhibition.